2015
DOI: 10.3329/agric.v12i2.21732
|View full text |Cite
|
Sign up to set email alerts
|

Response of Okra (<i>Abelmoschus esculentus</i> L.) to Growth Regulators and Organic Manures

Abstract: A study was conducted at the Horticulture Farm, Sher-e-Bangla Agricultural University, Bangladesh during April to September, 2012 to determine the suitability of selected plant growth regulators and the proper use and effectiveness of selected organic manures and also their suitable combinations for successful okra production. The experiment consisted of two factors: factor A: growth regulators as -G 0 : control (water), G 1 : GA 3 (100 ppm) and G 2 : Miraculan (1000 ppm) and factor B: organic manures as -OM 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Length of individual pod per plant was attained maximum (13.95 cm) from 100 ppm gibberellic acid application and minimum length of individual pod was observed (12.11 cm) with no gibberellic acid (Table 5). Uddin et al (2014), Mehraj et al (2015) and Chowdhury et al (2014) found same findings. Combination of different doses of cowdung and gibberellic acid was varied significantly on the pod length per plant.…”
Section: Green Pod Lengthmentioning
confidence: 56%
See 2 more Smart Citations
“…Length of individual pod per plant was attained maximum (13.95 cm) from 100 ppm gibberellic acid application and minimum length of individual pod was observed (12.11 cm) with no gibberellic acid (Table 5). Uddin et al (2014), Mehraj et al (2015) and Chowdhury et al (2014) found same findings. Combination of different doses of cowdung and gibberellic acid was varied significantly on the pod length per plant.…”
Section: Green Pod Lengthmentioning
confidence: 56%
“…As well as, the highest pod diameter was found 1.68 cm in 100 ppm gibberellic acid treated plant and it was found the lowest (1.48 cm) in 0 ppm gibberellic acid applied (Table 6). Mehraj et al (2015); Uddin et al (2014) and Chowdhury et al (2014) observed similar findings. The combined effect of different doses cowdung and different concentrations of gibberellic acid was significantly influenced on pod diameter.…”
Section: Green Pod Diametermentioning
confidence: 58%
See 1 more Smart Citation
“…It provides most of the macro and micronutrients, protects the soil against erosion, supplies the cementing agent for the formation of the desired soil aggregates and loosens the soil. The application of vermincompost and poultry manure further increases the yield and yield attributes of okra [6]. Organic matter in the form of compost is the decomposition of plant biomass that has been described through the activity of soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Successful okra production may contribute partially in solving vegetable scarcity in summer. Total production of okra was about 240 thousand tons from 7287.5 ha in 2009 and the average yield was about 3.38 t/ha in Bangladesh (Chowdhury et al, 2015). The requirements of fertilizers in okra are important for the early growth and total production of fruit yield.…”
Section: Introductionmentioning
confidence: 99%